Epidemiological profile and survival analysis of oral and oropharyngeal squamous cell carcinomas: a 10-year retrospective study (Research, Society and Development, 2022)
The aim of this study is to identify the epidemiology profile of oral squamous cell carcinoma in a population of patients treated at the Bom Pastor FHOMUV Hospital of Varginha, in the state of Minas Gerais, Brazil. To this end, the medical records of patients admitted between 2004 and 2014 were collected and analyzed. The variables analyzed were: age, gender, habits, tumor location, histological grade, tumor size, presence of lymph nodes and metastasis, staging, treatment and relapse. The population studied consisted of 310 patients. Men represent the majority of cases – 79.68% - with ages varying around 60 years. The most common tumor locations were tongue (40.32%), oropharynx (21.29%) and floor of mouth (12.90%). Regarding staging, 54.25% of patients were in stage IV, of which 41.92 % reached 5-year survival. Radiation combined with chemotherapy was the most prescribed treatment (32.90%). Statistically significant correlations were found between gender and age, gender and tumor location, and tumor location and age. Results suggest a need for the implementation of public policies to prevent and control oral cancer in the state of Minas Gerais, aiming at reducing the number of new cases, promoting early diagnostics and improving prognosis and treatment of such neoplasias.